An Epıdemıologıc Survey Usıng "Treatment Prıorıty Index" (Tpı) On Prımary Schoolchıldren In Konya - Enis Güray; Elif Ertaş; Metin Orhan; Cenk Doruk (Galenos Yayinevi, 1994)
The aim of this present study was to rank malocclusions and assess the need for orthodontic treatment in a group of primary schoolchildren aged between 6-12 years old. The students in Mustafa Hotamışlı primary school were examined to evaluate the prevalence of malocclusions and for this purpose the "Treatment Priority Index" (TPI) was used. TPI was based on the evaluation of the clinical examinations of primary schoolchildren. The items measured were describing the occlusal anomalies such as the incisor relationship horizontally and vertically, the occlusion of buccal segments and tooth displacement. This disorders were weighted according to the first molar relationship, mesio-neutro- and disto-occlusion. To assess the range of malocclusions the "Malocclusion Severity Estimate" (MSE) was also used. The TPI values for 27.74% of the population was between 0.27-0.99, for 32.30%, 1- 3.99, for 21.12%, 4-6.99, for 11.39%, 7- 9.99 and for 7.45%, ≥10. These results indicated us that, 60.4% of the primary schoolchildren showed normal (acceptable) occlusion, while 39.96% of them showed definite to very severe malocclusions. The differences between the TPI values of the boys and girls were not found statistically significant among the total population by using "student t" test. The TPI differences between ages were also examined by using "ANOVA" and the values between 6-12 ages were not found statistically significant. This study emphasises the necessity of preventive orthodontic and pedodontic applications, serving to a limited amound of patient in our area.